Effectiveness of Using School Management Information Systems to Improve Principal Performance - Nikmah, Siti Wasiatun; Rasiman, Rasiman; Violinda, Qristin (Journal of Educational Sciences, 2025)
As leaders in educational units, principals play an important role in the development of educational information systems in schools. This study aims to determine the effectiveness of using school management information systems to improve principal performance. The method used is Research and Development (R&D) with a Mixed Methods approach, combining quantitative and qualitative analysis. The development follows the ADDIE model through five stages: (1) analysis of potential and problems, (2) system design, (3) development, (4) testing, and (5) evaluation. Data were obtained through observation, interviews, expert validation questionnaires (material, media, and design), as well as limited trials and field tests in experimental and control schools. The results of the study indicate that the use of this system is very feasible, practical, and effective in improving the performance of school principals.